CRIME OF MONEY LAUNDERING: MODE, CHALLENGES AND LAW ENFORCEMENT - Hadi Purnomo; Tansah Rahmatullah (Sean Institute, 2023)
Money laundering is the process of processing the proceeds of crime to hide its illegal origins. The crime of money laundering has become a crime that has attracted much attention from the international community, including in Indonesia, and is always associated with organized crime and can be transnational in nature, such as crimes related to drugs, terrorism and corruption. Money laundering crimes have a very direct or indirect negative effect on the country's economy. The method used in this research uses a normative juridical research approach through the study of library materials using deductive reasoning methods. Money laundering, in the context of criminology, can be understood through the prism concept of crime proposed by Henry and Lanier. Anti-money laundering laws generally require recipients of funds to act with reasonable care in financial transactions. Indonesia has an independent institution called the Financial Transaction Reports and Analysis Center (PPATK) which has an important role in implementing policies to prevent and eradicate money laundering as well as building an anti-money laundering and anti-terrorism financing system in Indonesia. Law of the Republic of Indonesia Number 8 of 2010 regulates three types of money laundering crimes, first, active money laundering crimes, second, passive money laundering crimes, third, for those who enjoy the proceeds of money laundering crimes. Indonesia has a strong legal framework to tackle money laundering and terrorism financing and makes good use of financial information, domestic and international cooperation. Indonesia needs to focus more on improving asset recovery, risk-based supervision, and sanctions that are proportional and provide a deterrent effect. Indonesia needs to increase risk-based supervision, especially of money changers, money or value transfer services, as well as the non-financial sector, and implement sanctions that are effective and provide a deterrent effect in all sectors. Indonesia must also ensure accurate information about the true owners of all companies is available to law enforcement.